Effectiveness and safety of azithromycin 1.5% eye drops for mass treatment of active trachoma in a highly endemic district in Cameroon. Issue 1 (1st November 2020) - Bella, Assumpta Lucienne; Einterz, Ellen; Huguet, Pierre; Bensaid, Philippe; Amza, Abdou; Renault, Didier
Abstract : Objective: To evaluate the effectiveness and safety of azithromycin 1.5% eye drops under field conditions to reduce active trachoma in a highly endemic district in Cameroon. This is a follow-up of an initial report published in 2010. Methods and analysis: Three annual campaigns were performed in 2008, 2009 and 2010 to treat the population (~1 20 000 individuals) of the Kolofata Health District with topical azithromycin 1.5% (one drop in each eye, morning and evening for three consecutive days). The effectiveness of this intervention against active trachoma was assessed in children aged 1–9 years in cross-sectional studies prior to each mass treatment using a systematic sampling procedure (in 2008, 2009 and 2010) and then 1 year (2011) and 3 years (2013) after the last intervention among the villages with previously high active trachoma prevalence or never tested. Results: The prevalence of trachomatous inflammation—follicular (TF) dropped from 24.0% (95% CI 20.7 to 27.5) before treatment to 2.8% (95% CI 2.2 to 3.7) 1 year after completion of the 3 year campaign. Trachomatous inflammation—intense was present in only 4 (0.2%) children 1 year after the third round of treatment. Three years after the last campaign, the surveillance survey among the most prevalent villages and villages never tested before showed a prevalence of 5.2% (95% CI 3.6 to 7.2) of active trachoma. Tolerance was excellent, with no report of treatment interruption, serious ocular or systemic adverse events. Conclusion: Annual mass treatment with azithromycin eye drops was shown to be effective in reducing TF to a level ≤5% one year after a 3-round annual mass treatment in an endemic region at the district level.